Correlation between Insulin antibodyand HbA1c in Diabetes Mellitus - Sharad, Joumana; Mousa, Hind (University of Thi-Qar Journal of Science, 2024)
Insulin antibodies (INAs) are found in both types of diabetic patients and have low binding capacity and high affinity leading to hypoglycemia or hyperglycemia in type II patients taking insulin, which differs from the insulin antibodies found in type I that contain a high capacity of insulin binding  and low affinity. This work aims to detect the levels of insulin antibodies and HbA1c in diabetic patients, and find the correlation between them and its potential role in glucose control.  The study involved 60 patients with diabetes, divided into two groups type I and type II, each group containing 30 patients, in addition to 30 healthy individuals as a control group. High-performance liquid chromatography in a D-10 analyzer was used to measure HbA1c while ELISA was used to measure INAs in control and patients .Results: The current finding showed significant an elevated mean levels of HbA1c and INAs in both  of patients groups compare to healthy, and there was non-significant weak positive correlation between  them  (R=  0.107 ,  P= 0.4 ).Together, elevated levels of HbA1c and INA, and the positive correlation between their levels, provide evidence of the effect of insulin antibodies on glycemic control and the effects of HbA1c levels in patients with diabetes.